Inclusive community landscapes in rural midwestern cities: a design proposal for Emporia, Kansas - Molaskey, Katherine (Kansas State University, 2013)
The landscape has the opportunity to commemorate new, dynamic cultural identities which are developing in rural cities throughout the Midwest. These communities are experiencing historic demographic changes as a result of two major phenomena: the in-migration of foreign born peoples and the out-migration of younger generations. Immigrants are settling in rural cities because of the relatively low cost of living, available skilled and unskilled labor jobs, and developing immigrant networks. Foreign traditions and cultural ideals have introduced a new dimension to the historically homogeneous communities found in the Midwest. The age demographic is also changing as young adults move away from their rural hometowns seeking employment and education opportunities available in larger, metropolitan areas. This project will propose a research and design process for defining a design concept for Inclusive Community Landscapes in Midwestern rural cities with diverse population demographics. Inclusive Community Landscapes are purposefully programmed public spaces that celebrate the positive effects of immigration and an aging population: they are defined by the people of the rural city. The goals of these landscapes are to educate visitors about the history of the town, honor the diverse cultures that have been, are, and will be part of the town, and promote communication amongst residents. The project concludes with a design of an Inclusive Community Landscape in downtown Emporia, Kansas, a reflection on the applied research and design processes, and a revised process based on lessons learned during the project.
Keywords: Emporia, Kansas; Community; Inclusive; Rural; Landscape Architecture (0390)